The 16 macaques of the University of Modena have been adopted by LAV, an important case of reintegration of animals used for animal testing - Carla Campanaro (Universitat Autonoma de Barcelona. Facultat de Dret, 2017)
The 16 macaques that were owned by the University of Modena have been adopted by LAV, one of the most important animal rights NGOs in Italy.